PENGARUH PEMUPUKAN ANORGANIK TERHADAP KUALITAS UMBI BENIH BAWANG MERAH (THE EFFECTS OF ANORGANIC FERTILIZER TO SEED BULB QUALITY OF THE SHALLOTS) - Rajiman, Rajiman (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2010)
This research was aimed to study of effects of anorganic.fertilizer to seed bulb quality of shallots at coastal sandy land. The research was conducted with completelly block randomized design, which consists of two factors. The first factor was Urea+ZA level : 1/3, 2/3 and 1 dosages. The seconds factor was phosphor+potassium level : 1/3, 2/3 and 1 dosages. The fertiltzer recomendation were Urea of 150 kg.ha-1, ZA of 250 kg.ha-1, TSP and KCL of 15A kg.ha-1. To control was used land no fertilizer. The observation of parameters were bulb diameter, bulb hight, bulb color, bulb particle weight, solubility, total, content of N, P and K. The data were analysis by variances and orthogonal contras 5%. The results showed the usage anorganic fertilizer at coastal sandy land increased seed bulb quality of shallots. The increasing Urea+ZA and phospor+potassium level did not significant on seed bulb quaiity of shallot.